Actualización y reflexiones en sexología - Alejandro Villena-Moya; Fernando Muñoz-Montesinos; Iris Tolosa; Gabriel Serrano; Bárbara Ruiz; Gema Chenoll; Andrea Galarreta; Andrea Lucía Ladrón de Guevara; Gemma Mestre-Bach; Carlos Chiclana-Actis (Psicosomática y Psiquiatría, 2023)
Resumen